Photonic Structures in Biology: A Possible Blueprint for Nanotechnology - Frank P. Barrows; Michael H. Bartl (Nanomaterials and Nanotechnology)
Nature has had millions of years to optimize photonic crystals - an endeavour mankind only really began in the 1980s. Often, we attempt to mimic and expand upon nature’s designs in creating photonic structures that meet our technology-driven needs. While this strategy can be fruitful in fabricating novel architectures, one has to keep in mind that nature designed and optimized these structures for specific applications (e.g., colouration, camouflaging, signalling), but certainly not for use in photonic chips and optical circuits. To take full advantage of biological structures as blueprints for nanotechnology, it is important to understand the purpose and development of natural structural colours. In this review, we will discuss important aspects of the design, formation and evolution of the structures embedded in beetle exoskeletons that are responsible for their striking colouration. In particular, we will focus on the purpose of structural colours for camouflaging, mimicry and signalling. We will discuss their evolutionary and ecological development and compare the development of beetles with and without structural colours. Examples of non-colour-related structural functionalities will also be introduced and briefly discussed. Finally, a brief overview of nature’s synthesis strategies for these highly evolved structures will be given, with particular focus on membrane assembly.